Harnessing DNA Repair Defects to Augment Immune-Based Therapies in Triple-Negative Breast Cancer - Clark, Curtis A.; Yang, Eddy S. (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) has poor prognosis with limited treatment options, with little therapeutic progress made during the past several decades. DNA damage response (DDR) associated therapies, including radiation and inhibitors of DDR demonstrate potential efficacy against TNBC, especially under the guidance of genomic subtype-directed treatment. The tumor immune microenvironment also contributes greatly to TNBC malignancy and response to conventional and targeted therapies. Immunotherapy represents a developing trend in targeted therapies directed against TNBC and strategies combining immunotherapy and modulators of the DNA damage response pathways are being pursued. There is increasing understanding of the potential interplay between DNA damage response pathways and immune-associated signaling. As such, the question of how we treat triple-negative breast cancer regarding novel immuno-molecular strategies is continually evolving. In this review, we explore the current and upcoming treatment options of TNBC in the context of DNA repair mechanisms and immune-based therapies, with a focus on implications of recent genomic analyses and clinical trial findings.